Impact of bovine serum albumin – A protein corona on toxicity of ZnO NPs in environmental model systems of plant, bacteria, algae and crustaceans. (May 2021) - Janani, B.; Raju, Lija L.; Thomas, Ajith M.; Alyemeni, Mohammed Nasser; Dudin, Gani Asa; Wijaya, Leonard; Alsahli, Abdulaziz Abdullah; Ahmad, Parvaiz; Khan, S. Sudheer
Abstract: Zinc oxide nanoparticles (ZnO NPs) are widely applied in industrial, household and medical areas that lead to its discharge and accumulation in ecosystem. Here, the toxic effect of ZnO NPs in presence and absence of bovine serum albumin (BSA) was analyzed. The difference in toxicity of bare ZnO and BSA interacted ZnO was studied with different environmental models. P. aeruginosa and S. aureus were used as model bacterial systems. Toxicity against bacteria was determined by employing plate count method. C. pyrenoidsa was used as algal system for evaluating toxicity and it was determined by chlorophyll estimation assay. Daphnia sp. was chosen as crustacean system model. A. cepa root cells were chosen as plant model. ZnO NPs increased the ROS formation, lipid peroxidation and oxidative stress and it reduced in the presence of BSA. The cytotoxicity, chromosomal aberrations and micronuclei (MN) index of A. cepa were increased after ZnO NPs treatment. Same time the toxic effect was decreased in case of BSA coated ZnO NPs. The NPs toxic potential on the organisms decreased in the order of P. aeruginosa (LC50 –0.092 mg/L) >  S. aureus (LC50 –0.33 mg/L) >  Daphnia sp (LC50 –0.35 mg/L) >  C. pyrenoidosa (LC50 –8.17 mg/L). LC50 in presence of BSA was determined to be 18.45, 26.24, 17.27 and 53.97 mg/L for P. aeruginosa, S. aureus, Daphnia sp and C. pyrenoidosa respectively. Therefore, the report suggests that BSA stabilized ZnO NPs could be more amenable towards applications in biotechnology and bioengineering.